Measuring Subjective Quality of Life in Czech and Slovak Nurses: Validity of the Czech and Slovak Versions of Personal Wellbeing Index - ELENA GURKOVÁ; JOZEF DŽUKA; MÁRIA SOVÁRIOVÁ SOÓSOVÁ; KATARÍNA ŽIAKOVÁ; SYLVIE HAROKOVÁ; RADKA ŠERFELOVÁ (Journal of Social Research & Policy, 2012)
The aim of this study was to investigate the psychometric properties of the Slovak and Czech versions of the Personal Well-beingIndex (PWI) in population of nurses. The sample for study consisted of 1043 hospital staff nurses from 12 hospitals in the Czechand Slovak Republics. The data were collected using a set of questionnaires that included the Positive Affect Scale, the NegativeAffect Scale, and PWI. The PWI demonstrated good psychometric properties in terms of its factor structure, reliability, convergentand construct validity.